Prussian blue composite nanomaterial as well as preparation method and application thereof

By loading Prussian blue hollow spheres on MXene material and combining electrostatic self-assembly technology, the problem of insufficient desalination ability and cycle stability of electrode materials in capacitance deionization technology is solved, and efficient electrode material performance improvement is achieved.

CN119191482AActive Publication Date: 2024-12-27XIAN JIAOTONG LIVERPOOL UNIV

Patent Information

Application Number
CN202411305343.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Among the existing capacitive deionization technologies, the electrode materials of MXene and traditional carbon materials have insufficient desalination capacity and cycle life, especially when dealing with high concentrations of brine, and are susceptible to oxidation.

Method used

By loading the Prussian blue hollow sphere on the MXene material, the synergistic effect of the two can improve the conductivity and ion transmission performance of the material, alleviate structural distortion during the charging and discharging process, and modify the Prussian blue hollow sphere for electrostatic self-assembly with the MXene .

Benefits of technology

It significantly improves the desalting ability, rate and cycling stability of the electrode material, enhances the conductivity and ion diffusion ability, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191482A_ABST
    Figure CN119191482A_ABST
Patent Text Reader

Abstract

The invention provides a Prussian blue composite nanomaterial and a preparation method and application thereof, the Prussian blue composite nanomaterial comprises an MXene material and Prussian blue hollow spheres, and the Prussian blue hollow spheres are loaded on the surface of the MXene material. Through the synergistic effect of the Prussian blue hollow spheres and the MXene, the Prussian blue composite nanomaterial has high conductivity and rapid ion transmission performance, and the desalting capacity, the rate and the cycling stability of the material are improved; and meanwhile, structural distortion caused by the ginger Taylor effect in the charging and discharging process can be relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of capacitive deionization and relates to a Prussian blue composite nano material and a preparation method and application thereof. Background Art

[0002] Capacitive deionization (CDI) is an electrochemical desalination technology. Among many seawater desalination technologies, CDI has many advantages, such as low energy consumption, low maintenance cost, long service life and environmental friendliness. Electrode materials are an important component of capacitive deionization systems. In recent years, Faraday electrode materials have gradually replaced traditional carbon materials due to their different electrosorption principles and have shown stronger electrosorption capabilities.

[0003] As a typical Faraday material, MXene exhibits excellent conductivity and high capacity in CDI applications. However, the layered structure of MXene is prone to stacking problems and is easily oxidized during storage, so researchers hope to improve its desalination capacity and rate by modifying MXene or optimizing the etching method.

[0004] PBAs (Prussian blue analogs) are also a high-capacity faradaic electrode material. Their open framework structure and abundant sodium ion extraction / embedding channels give PBAs a high specific surface area, uniform active sites, and adjustable crystal structure. However, traditional Prussian blue analogs have poor conductivity, short cycle life, and still face many challenges when used to treat high-concentration brine.

[0005] Based on the above research, it is necessary to provide a Prussian blue composite nanomaterial, which has high conductivity and fast ion transport performance and can improve the desalination capacity, rate and cycle stability of electrode materials. Summary of the invention

[0006] The object of the present invention is to provide a Prussian blue composite nanomaterial and a preparation method and application thereof. The Prussian blue composite nanomaterial has high conductivity and fast ion transport performance through the synergistic effect of Prussian blue hollow spheres and MXene, thereby improving the desalination capacity, rate and cycle stability of the material, and can also alleviate the structural distortion caused by the Jan-Taylor effect during the charge and discharge process.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a Prussian blue composite nanomaterial, wherein the Prussian blue composite nanomaterial comprises a MXene material and Prussian blue hollow spheres, wherein the Prussian blue hollow spheres are loaded on the surface of the MXene material.

[0009] The present invention utilizes the high conductivity of MXene as a conductive substrate and loads Prussian blue hollow spheres on MXene. Through the synergistic effect of the two, the composite nanomaterial has high conductivity and rapid ion transport performance, thereby improving the desalination capacity, rate and cycle stability of the material. In addition, the Prussian blue hollow sphere structure is conducive to ion diffusion and can alleviate the structural distortion caused by the Jan-Taylor effect during the charge and discharge process.

[0010] Preferably, in the Prussian blue composite nanomaterial, the content of Prussian blue hollow spheres is 15-75wt%, for example, 15wt%, 30wt%, 45wt%, 60wt% or 75wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] Preferably, in the Prussian blue hollow spheres, the hollow volume accounts for 30-40% of the total volume of the Prussian blue hollow spheres, for example, it can be 30%, 32%, 34%, 36%, 38% or 40%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] In a second aspect, the present invention provides a method for preparing a Prussian blue composite nanomaterial, the preparation method comprising the following steps:

[0013] The MXene material, the Prussian blue hollow spheres and the solvent are mixed, and the solid and liquid are separated to obtain the Prussian blue composite nanomaterial.

[0014] Preferably, the Prussian blue hollow spheres are first modified to obtain positively charged Prussian blue hollow spheres and then mixed with MXene materials and solvents;

[0015] Preferably, the modification method comprises the following steps:

[0016] The Prussian blue hollow spheres, the solvent and the modifier are mixed to obtain positively charged Prussian blue hollow spheres, thereby completing the modification of the Prussian blue hollow spheres.

[0017] The present invention first modifies the Prussian blue hollow spheres to obtain positively charged Prussian blue hollow spheres, and then combines them with MXene materials, so that MXene and PBA can be composited through electrostatic self-assembly. If the MXene material and the Prussian blue hollow spheres are directly composited without modification, the negatively charged Prussian blue hollow spheres and the negatively charged MXene cannot be uniformly composited, thereby resulting in a decrease in desalination.

[0018] Preferably, the modifier comprises an amino group-containing silane compound.

[0019] The present invention adopts amino-containing silane compounds for modification. After amine modification, the Prussian blue hollow spheres have positively charged -NH2 functional groups on their surfaces, which can be compounded with the surface functional groups of MXene nanosheets (such as negatively charged -OH, -F and -O) through electrostatic forces during the composite process and exist in the final composite material.

[0020] Preferably, the amino-containing silane compound includes any one of 3-aminopropyltrimethoxysilane, 3-aminopropylsilane, N-(n-butyl)-3-aminopropyltrimethoxysilane, dimethylaminopropyltrimethoxysilane or diethylaminomethyltriethoxysilane, or a combination of at least two thereof.

[0021] Preferably, the mass ratio of the Prussian blue hollow spheres to the modifier is 1:(0.025-0.18), for example, it can be 1:0.025, 1:0.05, 1:0.1, 1:0.15, 1:0.17 or 1:0.18, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] The mass ratio of the Prussian blue hollow spheres to the modifier of the present invention affects the degree of modification. If the modifier is too little and the degree of modification is too low, the subsequent electrostatic self-assembly is incomplete, and the components in the composite material are unevenly distributed and poorly contacted, resulting in low conductivity and low ion adsorption. If the modifier is too much and the degree of modification is too high, the surface modifier is excessive, which affects the conductivity and the redox reaction rate and may destroy the Prussian blue structure.

[0023] Preferably, the temperature for mixing the Prussian blue hollow spheres, the solvent and the modifier is 55-75°C, for example, 55°C, 60°C, 70°C or 75°C, and the time is 3-5h, for example, 3h, 4h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the method for preparing the Prussian blue hollow spheres comprises the following steps:

[0025] (i) mixing an alcohol solvent and a metal source and subjecting them to a solvothermal reaction to obtain a precursor;

[0026] (ii) mixing and reacting ferrocyanide, the precursor in step (i) and a solvent to obtain the Prussian blue hollow spheres.

[0027] The present invention firstly conducts a solvothermal reaction between an alcohol solvent and a metal source to obtain a solid Prussian blue glycerate sphere, which is a precursor of preparing a hollow Prussian blue sphere by a self-template method. After the glycerate sphere is dissolved in water, the metal ions are slowly released and react with ferrocyanide [Fe(CN)6] 4-Anion exchange is performed to generate Prussian blue precipitate. As Prussian blue is continuously generated, glycerol ester is hydrolyzed, and the material gradually changes from a solid structure to a hollow structure, and finally Prussian blue hollow spheres are obtained.

[0028] Preferably, the alcohol solvent in step (i) comprises glycerol and / or isopropanol.

[0029] Preferably, the mass ratio of the alcohol solvent to the metal source in step (i) is (40-55):100, for example, 40:100, 45:100, 50:100 or 55:100, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the metal source in step (i) comprises a manganese source and / or a cobalt source.

[0031] Preferably, the temperature of the solvent thermal reaction in step (i) is 130-150°C, for example, 130°C, 140°C or 150°C, and the time is 1-3h, for example, 1h, 2h or 3h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the ferrocyanide in step (ii) comprises potassium hexacyanoferrate trihydrate.

[0033] Preferably, the reaction temperature in step (ii) is 80-100°C, for example, 80°C, 90°C or 100°C, and the reaction time is 3-5h, for example, 3h, 4h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the time for mixing the MXene material, the Prussian blue hollow spheres and the solvent is 0.5-1.5 h, for example, 0.5 h, 1.0 h or 1.5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the mass ratio of the MXene material to the Prussian blue hollow spheres is 1:(0.5-7), for example, it can be 1:0.5, 1:1, 1:1.5, 1:2, 1:3, 1:4, 1:5, 1:6 or 1:7, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the method for preparing the MXene material comprises mixing the Max material with an etching solution, solid-liquid separation and drying.

[0037] Preferably, the Max material comprises titanium carbide aluminum.

[0038] Preferably, the etching solution comprises hydrochloric acid and lithium fluoride.

[0039] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0040] (1) Mixing the Max material, hydrochloric acid and lithium fluoride, separating the solid and liquid and drying to obtain a MXene material;

[0041] (2) stirring and mixing glycerol, isopropanol, a manganese source and a cobalt source in a mass ratio of (5-10):(35-45):(70-80):(20-30), and then solvothermally reacting at 130-150° C. for 1-3 h, cooling, centrifuging and washing with ethanol to obtain a precursor;

[0042] The ferrocyanide, the precursor and the solvent are mixed and reacted at 80-100° C. for 3-5 hours, centrifuged and washed with ethanol and deionized water, and dried to obtain Prussian blue hollow spheres;

[0043] (3) mixing the Prussian blue hollow spheres, the solvent and the modifier described in step (2) at 55-75° C. for 3-5 hours to obtain positively charged Prussian blue hollow spheres;

[0044] The mass ratio of the Prussian blue hollow sphere to the modifier is 1:(0.025-0.18);

[0045] (4) dispersing the MXene material described in step (1) in deionized water to obtain solution A, dispersing the positively charged Prussian blue hollow spheres described in step (3) in deionized water to obtain solution B, stirring and mixing solution A and solution B for 0.5-1.5h, washing with ethanol and deionized water after centrifugation, and freeze-drying to obtain the Prussian blue composite nanomaterial;

[0046] The mass ratio of the MXene material to the positively charged Prussian blue hollow spheres is 1:(0.5-2.5).

[0047] In a third aspect, the present invention provides a capacitive deionization device, wherein the capacitive deionization device comprises the Prussian blue composite nanomaterial as described in the first aspect.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The present invention adopts the high conductivity of MXene as a conductive substrate and loads Prussian blue hollow spheres on MXene. Through the synergistic effect of the two, the composite nanomaterial has high conductivity and fast ion transmission performance, thereby improving the desalination ability, rate and cycle stability of the material; in addition, the Prussian blue hollow sphere structure is conducive to ion diffusion and can alleviate the structural distortion caused by the Jan-Taylor effect during the charge and discharge process. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 TEM image of the Prussian blue hollow spheres described in Example 1 of the present invention;

[0051] Figure 2 This is a SEM image of the Prussian blue composite nanomaterial described in Example 1 of the present invention;

[0052] Figure 3 This is the XRD diagram of the Prussian blue composite nanomaterial and the Mxene material described in Example 1 of the present invention;

[0053] Figure 4 This is the EIS graph of the Prussian blue composite nanomaterial described in Example 1 of the present invention;

[0054] Figure 5 This is a CV graph of the Prussian blue composite nanomaterial described in Example 1 of the present invention;

[0055] Figure 6 This is a curve diagram of the change in conductivity over time of the Prussian blue composite nanomaterial during desalination described in Example 1 of the present invention. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0057] Example 1

[0058] This embodiment provides a Prussian blue composite nanomaterial, the Prussian blue composite nanomaterial includes a MXene material and Prussian blue hollow spheres, the Prussian blue hollow spheres are loaded on the surface of the MXene material, the content of the Prussian blue hollow spheres in the Prussian blue composite nanomaterial is 50%, and the hollow volume of the Prussian blue hollow spheres accounts for 32.5% of the total volume of the Prussian blue hollow spheres;

[0059] The preparation method of the Prussian blue composite nanomaterial comprises the following steps:

[0060] (1) Preparation of MXene materials

[0061] Mix 40 mL of 9 mol / L hydrochloric acid and 3 g of lithium fluoride, and stir magnetically at room temperature for 15 minutes until completely dissolved;

[0062] 1 g of titanium aluminum carbide (Ti3AlC2) powder was slowly added to the above solution at a uniform speed within 20 minutes, and the container was sealed and magnetically stirred at 35°C for 24 hours, followed by centrifugal filtration and washing for multiple times, with the centrifugal speed gradually increased from 4000 rpm until the pH value of the supernatant was greater than 6;

[0063] The collected precipitate was added with 60 mL of deionized water, ultrasonicated for 30 minutes until completely dissolved, centrifuged at 3000 rpm for 20 minutes, and the supernatant was collected and freeze-dried for 48 hours to obtain a black flaky MXene material.

[0064] (2) Preparation of Prussian blue hollow spheres

[0065] 75.3 mg of manganese nitrate tetrahydrate and 21.8 mg of cobalt nitrate hexahydrate were added to 8 mL of glycerol and 40 mL of isopropanol, and the mixture was stirred magnetically for 20 minutes, and then subjected to solvothermal reaction at 140 °C for 2 hours. After cooling to room temperature, the precipitate was collected by centrifugation and washed with ethanol several times to obtain a precursor.

[0066] The precursor was added to 200 mL of ethanol and ultrasonicated for 15 minutes until completely dissolved to obtain a first solution. 3.2 mmol of potassium hexacyanoferrate (II) trihydrate was added to 120 mL of deionized water to obtain a second solution. The second solution was added to the first solution under stirring conditions, and a straight condenser was added to reflux in an oil bath at 90°C for 4 hours. The precipitate was collected after centrifugation and washed with ethanol and deionized water for multiple times, and baked at 60°C for 2 hours to obtain Prussian blue hollow sphere powder.

[0067] The mass ratio of the glycerol, isopropanol, manganese nitrate tetrahydrate and cobalt nitrate hexahydrate is 8:40:75.3:21.8;

[0068] (3) Modification of Prussian blue hollow spheres

[0069] 5 mg of the Prussian blue hollow sphere powder of step (2) was added to 50 mL of deionized water, and ultrasonically dispersed until completely dissolved, and 0.5 mL of 3-aminopropyltrimethoxysilane was added, and refluxed at 65 ° C for 4 h to obtain positively charged Prussian blue hollow spheres;

[0070] The mass ratio of the Prussian blue hollow spheres to 3-aminopropyltrimethoxysilane is 1:0.1;

[0071] (4) Preparation of Prussian blue composite nanomaterials

[0072] Ultrasonic dispersion of 10 mg of the MXene material of step (1) in deionized water to obtain solution A, dispersion of 10 mg of the positively charged Prussian blue hollow spheres of step (3) in deionized water to obtain solution B, magnetic stirring of solution A and solution B for 1 h, centrifugation and washing with ethanol and deionized water for multiple times, then collecting the precipitate, freeze-drying for 48 hours, to obtain the Prussian blue composite nanomaterial PBA@MXene;

[0073] The mass ratio of the MXene material to the positively charged Prussian blue hollow spheres is 1:1;

[0074] The TEM image of the Prussian blue hollow sphere is as follows: Figure 1 As shown in the SEM images Figure 2 As shown, the EIS diagram is Figure 4 As shown, the CV diagram is Figure 5 As shown, the XRD patterns of the Prussian blue composite nanomaterial and the MXene material are as follows Figure 3 shown.

[0075] Example 2

[0076] This embodiment provides a Prussian blue composite nanomaterial, the Prussian blue composite nanomaterial includes a MXene material and Prussian blue hollow spheres, the Prussian blue hollow spheres are loaded on the surface of the MXene material, the content of the Prussian blue hollow spheres in the Prussian blue composite nanomaterial is 33%, and the hollow volume of the Prussian blue hollow spheres accounts for 30% of the total volume of the Prussian blue hollow spheres;

[0077] The preparation method of the Prussian blue composite nanomaterial comprises the following steps:

[0078] (1) Preparation of MXene materials

[0079] Mix 40 mL of 9 mol / L hydrochloric acid and 3 g of lithium fluoride, and stir magnetically at room temperature for 15 minutes until completely dissolved;

[0080] 1 g of titanium aluminum carbide (Ti3AlC2) powder was slowly added to the above solution at a uniform speed within 20 minutes, and the container was sealed and magnetically stirred at 35°C for 24 hours, followed by centrifugal filtration and washing for multiple times, with the centrifugal speed gradually increased from 4000 rpm until the pH value of the supernatant was greater than 6;

[0081] The collected precipitate was added with 60 mL of deionized water, ultrasonicated for 30 minutes until completely dissolved, centrifuged at 3000 rpm for 20 minutes, and the supernatant was collected and freeze-dried for 48 hours to obtain a black flaky MXene material.

[0082] (2) Preparation of Prussian blue hollow spheres

[0083] 70 mg of manganese nitrate tetrahydrate and 30 mg of cobalt nitrate hexahydrate were added to 5 mL of glycerol and 45 mL of isopropanol, and the mixture was stirred magnetically for 20 minutes, and then subjected to solvothermal reaction at 130 °C for 3 hours. After cooling to room temperature, the precipitate was collected by centrifugation and washed with ethanol for several times to obtain a precursor.

[0084] The precursor was added to 200 mL of ethanol and ultrasonicated for 15 minutes until completely dissolved to obtain a first solution. 3.2 mmol of potassium hexacyanoferrate (II) trihydrate was added to 120 mL of deionized water to obtain a second solution. The second solution was added to the first solution under stirring conditions, and a straight condenser was added to reflux in an oil bath at 100°C for 3 hours. The precipitate was collected after centrifugation and washed with ethanol and deionized water for multiple times, and baked at 60°C for 2 hours to obtain Prussian blue hollow spheres.

[0085] The mass ratio of the glycerol, isopropanol, manganese nitrate tetrahydrate and cobalt nitrate hexahydrate is 5:45:70:30;

[0086] (3) Modification of Prussian blue hollow spheres

[0087] 5 mg of the Prussian blue hollow sphere powder of step (2) was added to 50 mL of deionized water, and ultrasonically dispersed until completely dissolved, and 0.125 mL of 3-aminopropyltrimethoxysilane was added, and refluxed at 75 ° C for 3 h to obtain positively charged Prussian blue hollow spheres;

[0088] The mass ratio of the Prussian blue hollow spheres to 3-aminopropyltrimethoxysilane is 1:0.025;

[0089] (4) Preparation of Prussian blue composite nanomaterials

[0090] Ultrasonic dispersion of 10 mg of the MXene material of step (1) in deionized water to obtain solution A, dispersion of 5 mg of the positively charged Prussian blue hollow spheres of step (3) in deionized water to obtain solution B, magnetic stirring of solution A and solution B for 1.5 h, centrifugation, washing with ethanol and deionized water for multiple times, collecting the precipitate, and freeze-drying for 48 hours to obtain the Prussian blue composite nanomaterial;

[0091] The mass ratio of the MXene material to the positively charged Prussian blue hollow spheres is 1:0.5.

[0092] Example 3

[0093] This embodiment provides a Prussian blue composite nanomaterial, the Prussian blue composite nanomaterial includes a MXene material and Prussian blue hollow spheres, the Prussian blue hollow spheres are loaded on the surface of the MXene material, the content of the Prussian blue hollow spheres in the Prussian blue composite nanomaterial is 67%, and the hollow volume of the Prussian blue hollow spheres accounts for 40% of the total volume of the Prussian blue hollow spheres;

[0094] The preparation method of the Prussian blue composite nanomaterial comprises the following steps:

[0095] (1) Preparation of MXene materials

[0096] Mix 40 mL of 9 mol / L hydrochloric acid and 3 g of lithium fluoride, and stir magnetically at room temperature for 15 minutes until completely dissolved;

[0097] 1 g of titanium aluminum carbide (Ti3AlC2) powder was slowly added to the above solution at a uniform speed within 20 minutes, and the container was sealed and magnetically stirred at 35°C for 24 hours, followed by centrifugal filtration and washing for multiple times, with the centrifugal speed gradually increased from 4000 rpm until the pH value of the supernatant was greater than 6;

[0098] The collected precipitate was added with 60 mL of deionized water, ultrasonicated for 30 minutes until completely dissolved, centrifuged at 3000 rpm for 20 minutes, and the supernatant was collected and freeze-dried for 48 hours to obtain a black flaky MXene material.

[0099] (2) Preparation of Prussian blue hollow spheres

[0100] 80 mg of manganese nitrate tetrahydrate and 20 mg of cobalt nitrate hexahydrate were added to 10 mL of glycerol and 35 mL of isopropanol, and the mixture was stirred magnetically for 20 minutes, and then subjected to solvothermal reaction at 150° C. for 1 hour. After cooling to room temperature, the mixture was centrifuged and washed with ethanol for several times, and the precipitate was collected to obtain a precursor.

[0101] The precursor was added to 200 mL of ethanol and ultrasonicated for 15 minutes until completely dissolved to obtain a first solution. 3.2 mmol of potassium hexacyanoferrate (II) trihydrate was added to 120 mL of deionized water to obtain a second solution. The second solution was added to the first solution under stirring conditions, and a straight condenser was added to reflux in an oil bath at 80°C for 5 hours. The precipitate was collected after centrifugation and washed with ethanol and deionized water for multiple times, and baked at 60°C for 2 hours to obtain Prussian blue hollow spheres.

[0102] The mass ratio of the glycerol, isopropanol, manganese nitrate tetrahydrate and cobalt nitrate hexahydrate is 10:35:80:20;

[0103] (3) Modification of Prussian blue hollow spheres

[0104] 5 mg of the Prussian blue hollow sphere powder of step (2) was added to 50 mL of deionized water, and ultrasonically dispersed until completely dissolved, and 1.25 mL of 3-aminopropyltrimethoxysilane was added, and refluxed at 55 ° C for 5 h to obtain positively charged Prussian blue hollow spheres;

[0105] The mass ratio of the Prussian blue hollow spheres to 3-aminopropyltrimethoxysilane is 1:0.18;

[0106] (4) Preparation of Prussian blue composite nanomaterials

[0107] Ultrasonic dispersion of 10 mg of the MXene material of step (1) in deionized water to obtain solution A, dispersion of 20 mg of the positively charged Prussian blue hollow spheres of step (3) in deionized water to obtain solution B, magnetic stirring of solution A and solution B for 0.5 h, centrifugation and washing with ethanol and deionized water for multiple times, then collecting the precipitate, freeze-drying for 48 hours, to obtain the Prussian blue composite nanomaterial;

[0108] The mass ratio of the MXene material to the positively charged Prussian blue hollow spheres is 1:2.

[0109] Example 4

[0110] This embodiment provides a Prussian blue composite nanomaterial, which is the same as that of Embodiment 1 except that in the preparation method thereof, the mass ratio of the MXene material and the positively charged Prussian blue hollow spheres in step (4) is 1:0.2, so that the adaptability of the obtained Prussian blue composite nanomaterial changes.

[0111] Example 5

[0112] This embodiment provides a Prussian blue composite nanomaterial, which is the same as that of Embodiment 1 except that in the preparation method thereof, the mass ratio of the MXene material and the positively charged Prussian blue hollow spheres in step (4) is 1:2.5, so that the adaptability of the obtained Prussian blue composite nanomaterial changes.

[0113] Example 6

[0114] This embodiment provides a Prussian blue composite nanomaterial, which is the same as that of Embodiment 1 except that in the preparation method thereof, the mass ratio of the MXene material and the positively charged Prussian blue hollow spheres in step (4) is 1:3.5, so that the adaptability of the obtained Prussian blue composite nanomaterial changes.

[0115] Example 7

[0116] This embodiment provides a Prussian blue composite nanomaterial, which is the same as that of Embodiment 1 except that in the preparation method thereof, the mass ratio of the MXene material and the positively charged Prussian blue hollow spheres in step (4) is 1:5, so that the adaptability of the obtained Prussian blue composite nanomaterial changes.

[0117] Example 8

[0118] This embodiment provides a Prussian blue composite nanomaterial, which is the same as that of Embodiment 1 except that in the preparation method thereof, the mass ratio of the MXene material and the positively charged Prussian blue hollow spheres in step (4) is 1:7, so that the adaptability of the obtained Prussian blue composite nanomaterial changes.

[0119] Example 9

[0120] This embodiment provides a Prussian blue composite nanomaterial. The Prussian blue composite nanomaterial is the same as that in Embodiment 1 except that in the preparation method thereof, the mass ratio of the Prussian blue hollow spheres to 3-aminopropyltrimethoxysilane in step (3) is 1:0.01, so that the adaptability of the obtained Prussian blue composite nanomaterial changes.

[0121] Example 10

[0122] This embodiment provides a Prussian blue composite nanomaterial. The Prussian blue composite nanomaterial is the same as that in Embodiment 1, except that the mass ratio of the Prussian blue hollow spheres to 3-aminopropyltrimethoxysilane in step (3) of the preparation method is 1:0.4, so that the adaptability of the obtained Prussian blue composite nanomaterial changes.

[0123] Embodiment 11

[0124] This embodiment provides a Prussian blue composite nanomaterial, which is the same as that of Embodiment 1 except that the modification in step (3) is not performed in the preparation method to change the adaptability of the obtained Prussian blue composite nanomaterial.

[0125] Comparative Example 1

[0126] This comparative example provides a Prussian blue material, which is the same as Example 1 except that the MXene material is not included;

[0127] The preparation method of the Prussian blue material is the same as that of Example 1 except that step (1) and step (4) are not performed.

[0128] Comparative Example 2

[0129] This comparative example provides a MXene material, which is the same as Example 1 except that the MXene material does not include Prussian blue hollow spheres;

[0130] The preparation method of the MXene material is the same as that of Example 1, except that steps (2) to (4) are not performed.

[0131] Comparative Example 3

[0132] This comparative example provides a Prussian blue composite nanomaterial, which is the same as Example 1 except that the Prussian blue hollow spheres are replaced by Prussian blue solid spheres;

[0133] The preparation method of the Prussian blue composite nanomaterial is the same as that of Example 1 except that step (2) is the preparation of Prussian blue solid spheres. The preparation method of the Prussian blue solid spheres comprises:

[0134] (1) adding 4.5 mmol sodium citrate dihydrate to 100 mL deionized water, stirring magnetically until completely dissolved, then adding 225.9 mg manganese nitrate tetrahydrate and 65.4 mg cobalt nitrate hexahydrate, stirring magnetically to obtain a first solution;

[0135] (2) 9.6 mmol potassium hexacyanoferrate (II) trihydrate was added to 100 mL deionized water and magnetically stirred for 30 minutes to obtain a second solution. The second solution was added to the first solution, magnetically stirred for 10 minutes, aged at room temperature for 24 hours, centrifuged and washed with ethanol and deionized water for multiple times, and then the precipitate was collected and baked at 60°C for 6 hours to obtain Prussian blue nanocube powder.

[0136] The Prussian blue composite nanomaterials prepared in the above Examples 1-8 and Comparative Example 3, the Prussian blue material prepared in Comparative Example 1, and the MXene material prepared in Comparative Example 2 were used as electrode materials, respectively mixed with carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and the mixture was stirred into a slurry with N-methylpyrrolidone as a solvent, and applied to an area of ​​about 2cm*2cm in the middle of the graphite paper to form an electrode sheet of the CDI electrode, and baked at 60°C for 12 hours. The CDI performance test used the electrode sheet prepared above as the anode, the activated carbon as the cathode, the electrode mass was about 30mg, and the sodium chloride solution was set to about 1000us cm -1 , the solution volume is 40mL, the rotation speed is 100rpm, the test voltage range is -1.4V-1.4V, and the electrode material is analyzed at a current density of 20mAg -1 The desalination amount at the time of the test was measured, and the changes of current, voltage and conductivity over time were recorded every 10 seconds. The conductivity-time change curve of Example 1 during desalination was measured as shown in the figure Figure 6 As shown, it exhibits excellent desalination performance.

[0137] The desalination amount obtained by the test is shown in Table 1:

[0138] Table 1

[0139]

[0140]

[0141] From Table 1 we can see that:

[0142] It can be seen from Example 1 and Comparative Examples 1-2 that the MXene material of the present invention and the Prussian blue hollow spheres are composited to exert a synergistic effect of the two and obtain a Prussian blue composite nanomaterial with good desalination performance; it can be seen from Example 1 and Comparative Example 3 that when Prussian blue is a solid material, the ion diffusion capacity decreases, and the Jan-Taylor effect is serious during the charging and discharging process, which will affect the performance of the Prussian blue composite nanomaterial; it can be seen from Example 1 and Examples 4-8 that the amount of Prussian blue hollow spheres loaded on the surface of the MXene material of the present invention will also affect the effect of the two, thereby affecting the performance of the composite nanomaterial; it can be seen from Example 1 and Examples 9-10 that the degree of modification of the Prussian blue hollow spheres will affect its composite with the MXene material, thereby affecting the performance of the composite nanomaterial; it can be seen from Example 1 and Example 11 that if the Prussian blue hollow spheres are not modified, it cannot be electrostatically self-assembled with the MXene material, thereby affecting the composite of the two.

[0143] In summary, the present invention provides a Prussian blue composite nanomaterial and a preparation method and application thereof. The Prussian blue composite nanomaterial has high conductivity and fast ion transport performance through the synergistic effect of Prussian blue hollow spheres and MXene, thereby improving the desalination ability, rate and cycle stability of the material, and can also alleviate the structural distortion caused by the Jan-Taylor effect during the charge and discharge process.

[0144] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A Prussian blue composite nanomaterial, characterized in that: The Prussian blue composite nanomaterial comprises a MXene material and Prussian blue hollow spheres, and the Prussian blue hollow spheres are loaded on the surface of the MXene material.

2. The Prussian blue composite nanomaterial according to claim 1, characterized in that: In the Prussian blue composite nanomaterial, the content of Prussian blue hollow spheres is 15-75wt%; Preferably, in the Prussian blue hollow spheres, the hollow volume accounts for 30-40% of the total volume of the Prussian blue hollow spheres.

3. A method for preparing the Prussian blue composite nanomaterial as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: The MXene material, the Prussian blue hollow spheres and the solvent are mixed, and the solid and liquid are separated to obtain the Prussian blue composite nanomaterial.

4. The preparation method according to claim 3, characterized in that: The Prussian blue hollow spheres are first modified to obtain positively charged Prussian blue hollow spheres, which are then mixed with MXene materials and solvents; Preferably, the modification method comprises the following steps: The Prussian blue hollow spheres, the solvent and the modifier are mixed to obtain positively charged Prussian blue hollow spheres, thereby completing the modification of the Prussian blue hollow spheres.

5. The preparation method according to claim 4, characterized in that: The modifier includes an amino-containing silane compound; Preferably, the amino-containing silane compound includes any one of 3-aminopropyltrimethoxysilane, 3-aminopropylsilane, N-(n-butyl)-3-aminopropyltrimethoxysilane, dimethylaminopropyltrimethoxysilane or diethylaminomethyltriethoxysilane, or a combination of at least two thereof; Preferably, the mass ratio of the Prussian blue hollow sphere to the modifier is 1:(0.025-0.18); Preferably, the Prussian blue hollow spheres, the solvent and the modifier are mixed at a temperature of 55-75° C. and a time of 3-5 hours.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The method for preparing the Prussian blue hollow sphere comprises the following steps: (i) mixing an alcohol solvent and a metal source and subjecting them to a solvothermal reaction to obtain a precursor; (ii) mixing and reacting ferrocyanide, the precursor in step (i) and a solvent to obtain the Prussian blue hollow spheres.

7. The preparation method according to claim 6, characterized in that: The alcohol solvent in step (i) includes glycerol and / or isopropanol; Preferably, the mass ratio of the alcohol solvent to the metal source in step (i) is (40-55):100; Preferably, the metal source in step (i) comprises a manganese source and / or a cobalt source; Preferably, the temperature of the solvent thermal reaction in step (i) is 130-150° C. and the time is 1-3 h; Preferably, the ferrocyanide in step (ii) comprises potassium hexacyanoferrate trihydrate; Preferably, the reaction temperature in step (ii) is 80-100° C. and the reaction time is 3-5 h.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The time for mixing the MXene material, the Prussian blue hollow spheres and the solvent is 0.5-1.5 hours; Preferably, the mass ratio of the MXene material to the Prussian blue hollow sphere is 1:(0.5-7); Preferably, the method for preparing the MXene material comprises mixing the Max material with an etching solution, solid-liquid separation, and drying; Preferably, the Max material comprises titanium carbide aluminum; Preferably, the etching solution comprises hydrochloric acid and lithium fluoride.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The preparation method comprises the following steps: (1) Mixing the Max material, hydrochloric acid and lithium fluoride, separating the solid and liquid and drying to obtain a MXene material; (2) stirring and mixing glycerol, isopropanol, a manganese source and a cobalt source in a mass ratio of (5-10):(35-45):(70-80):(20-30), and then solvothermally reacting at 130-150° C. for 1-3 h, cooling and centrifuging, and washing with ethanol to obtain a precursor; The ferrocyanide, the precursor and the solvent are mixed and reacted at 80-100° C. for 3-5 hours, centrifuged and washed with ethanol and deionized water, and dried to obtain Prussian blue hollow spheres; (3) mixing the Prussian blue hollow spheres, the solvent and the modifier described in step (2) at 55-75° C. for 3-5 hours to obtain positively charged Prussian blue hollow spheres; The mass ratio of the Prussian blue hollow sphere to the modifier is 1:(0.025-0.18); (4) dispersing the MXene material described in step (1) in deionized water to obtain solution A, dispersing the positively charged Prussian blue hollow spheres described in step (3) in deionized water to obtain solution B, stirring and mixing solution A and solution B for 0.5-1.5h, washing with ethanol and deionized water after centrifugation, and freeze-drying to obtain the Prussian blue composite nanomaterial; The mass ratio of the MXene material to the positively charged Prussian blue hollow spheres is 1:(0.5-2.5).

10. A capacitive deionization device, characterized in that: The capacitive deionization device comprises the Prussian blue composite nanomaterial as claimed in claim 1 or 2.

Citation Information

Patent Citations

  • Silicon dioxide-coated prussian blue analogue nano-particles and preparation method and application thereof

    CN105343903A

  • Spherical material with cobalt glycerol core and iron cobalt prussian blue analogue shell as well as preparation and application of spherical material

    CN114899367A

  • Self-supporting negative electrode material and preparation method thereof, negative electrode plate and secondary battery

    CN114914427A

Cited By

  • High-entropy Prussian blue analogue composite MXene electrode material and preparation method and application thereof

    CN120423652A

  • Composite electrode material for electrochemical desalination and preparation method and application thereof

    CN121494151A